Mechanisms of soil organic matter formation for perennial grain Kernza® under contrasting nitrogen management - van der Pol, Laura K.; Crews, Timothy E.; Cotrufo, M. Francesca (Frontiers in Soil Science, 2025)
Restoring soil organic matter (SOM) in arable land is considered one of the best natural solutions to sustain food production and mitigate climate change. With typically deep, robust root systems compared to annual grains, perennial systems are likely to promote soil organic carbon (C) sequestration while offering many ecosystem co-benefits. The intermediate wheatgrass domesticated for grain production as Kernza® (Thinopyrum intermedium) is the first perennial grain available to US growers. We quantified the formation of SOM over 2 years from the roots and shoots of Kernza grown alone and in an alfalfa (Medicago sativa) intercrop using continuously 13C- and 15N-labeled plant material. We compared SOM formation of the Kernza tissues under three contrasting agronomic environments: (1) unfertilized Kernza monoculture, (2) unfertilized Kernza biculture with nitrogen (N)-fixing alfalfa, and (3) fertilized (100 kg N ha−1 year−1) Kernza monoculture. We hypothesized that the management and plant tissues with higher N would enhance mineral associated organic matter (MAOM) formation by alleviating microbial N-limitation and leading to enhanced efficiency of microbial residue transformation. Furthermore, we hypothesized that root tissues would contribute to SOM formation primarily as occluded particulate organic matter (oPOM) due to their chemistry and interface with the soil matrix. We found that overall Kernza promoted new SOM formation with 14% of roots and 8% of shoot-derived C recovered in bulk soil after 27 months compared to 5% for alfalfa roots and shoots. There were no differences between the efficiency of MAOM formation of alfalfa vs. Kernza. The intercrop sustained similar C and N stocks to the fertilized treatment, although we found little evidence that N management was a major influence on SOM formation. Of the Kernza root tissue C incorporated into SOM, we found 3.5% in MAOM and 6% in oPOM, implying that 9.5% of root tissue C inputs may be stabilized in the soil. Legume intercrops can support Kernza cropping systems with minimal synthetic inputs, although in our study, they did not lead to enhanced SOM formation even with comparable levels of productivity.